Stirring‐Free Scalable Electrosynthesis Enabled by Alternating Current. Issue 18 (24th February 2023) - Bortnikov, Evgeniy O.; Smith, Barbara S.; Volochnyuk, Dmitriy M.; Semenov, Sergey N.
Abstract: Alternating current (AC) electrolysis is receiving increased interest as a versatile tool for mild and selective electrochemical transformations. This work demonstrates that AC can enable the concept of a stirring‐free electrochemical reactor where the periodic switch of electrode polarity, inherent to AC, provides uniform electrolysis across the whole volume of the reactor. Such design implies a straightforward approach for scaling up electrosynthesis. This was demonstrated on the range of electrochemical transformations performed in three different RVC‐packed reactors on up to a 50‐mmol scale. Redox‐neutral, oxidative, and reductive processes were successfully implemented using the suggested design and the applicable frequency ranges were further investigated for different types of reactions. The advantages of the AC‐enabled design – such as the absence of stirring and a maximized surface area of the electrodes – provide the possibility for its universal application both for small‐scale screening experimentation and large‐scale preparative electrosynthesis without significant optimization needed in between. Abstract : The use of alternating current enables the concept of a stirring‐free batch reactor, where the periodic switch of electrode polarity provides uniform electrolysis throughout the reactor volume. The AC‐derived design implies a straightforward approach for scaling up electrosynthesis from parallel screening experiments to large‐scale preparative electrolysis.